2013
DOI: 10.1007/978-1-62703-730-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Application of Riboswitch-Based Sensors That Detect Metabolites Within Bacterial Cells

Abstract: A riboswitch is an RNA element that detects the level of a specific metabolite within the cell and regulates the expression of co-transcribed genes. By fusing a riboswitch to a reporter protein in a carefully designed and tested construct, this ability can be exploited to create an intracellular sensor that detects the level of a particular small molecule within live bacterial cells. There is a great deal of flexibility in the design of such a sensor and factors such as the molecule to be detected and the down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…While this particular set of theophylline-responsive riboswitches has proven to be effective in many different bacterial species, the potential for developing novel riboswitches is significant. In addition to selecting aptamers against exogenously added ligands, riboswitches that respond to endogenous signals generated within the cell can be developed to form feedback circuits within the cell (39). The modular nature and small size of riboswitches make them attractive targets for engineering or evolving riboswitches with new properties.…”
Section: Discussionmentioning
confidence: 99%
“…While this particular set of theophylline-responsive riboswitches has proven to be effective in many different bacterial species, the potential for developing novel riboswitches is significant. In addition to selecting aptamers against exogenously added ligands, riboswitches that respond to endogenous signals generated within the cell can be developed to form feedback circuits within the cell (39). The modular nature and small size of riboswitches make them attractive targets for engineering or evolving riboswitches with new properties.…”
Section: Discussionmentioning
confidence: 99%
“…Aptamer as a recognition element is combined with downstream gene expression as a reporter to realize the spatial, temporal, and dose‐dependent regulation of the target. This interaction between the aptamer recognition element and the reporter is guided by the way they are written into the DNA blueprint of the biosensor (Fowler & Li, 2014). Moreover, benefiting from the target versatility of aptamer, riboswitch, as the gene structure of reporter protein, can achieve the purpose of highly sensitive and specific detection from small organic molecules to heavy metals, proteins, cells, and even complete virus particles (Oueslati et al., 2018; Qi et al., 2022; Stepanova et al., 2017; Sun et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Reporter systems that rely on gene expression often require a longer time to produce a detectable signal. For example, riboswitch reporters have been observed to respond in the time range of 3−24 h. 7,14,15 A time-dependent study of a riboswitch-based dual-color sensor that changes color upon ligand binding revealed that the minimum time required for response is 4 h. 16 Engineered aptazymes show fast cleavage kinetics in vitro in the presence of the target ligands, 6,17 but similarly long incubation times (20−72 h) have been reported to see changes in aptazyme-controlled GFP and luciferase reporters in bacterial or mammalian cells. 6,11,18 Recently, genetically encodable RNA-based fluorescent (RBF) biosensors composed of a ligand-binding riboswitch aptamer fused to an in vitro selected fluorogenic aptamer have emerged as a promising alternative tool.…”
mentioning
confidence: 99%